1991
DOI: 10.1161/01.cir.84.1.400
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil accumulation in ischemic canine myocardium. Insights into time course, distribution, and mechanism of localization during early reperfusion.

Abstract: Background. We have previously demonstrated that chemotactic factors released from the ischemic canine myocardium peak early during reperfusion and that they elicit neutrophil adherence reactions in vitro that are dependent on the CD18 glycoprotein family. In this study we investigated the hypothesis that neutrophil localization in ischemic canine myocardium in vivo occurs over a similar time course during early reperfusion and involves a CD18-dependent mechanism.Methods and Results. We occluded the circumflex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
95
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(104 citation statements)
references
References 17 publications
6
95
1
2
Order By: Relevance
“…Because leukocyte adhesion and transmigration might induce genes in the endothelium either through paracrine cytokine secretion mechanisms or through direct stimulation associated with adhesion, we chose to examine MCP-1 induction in a model using brief, nonlethal ischemia followed by reperfusion that has been well characterized in the past as inducing ROI formation and secretion from myocytes associated with dysfunction but no cell death. 5,[12][13][14] We have also confirmed that there is no significant leukocyte infiltration associated with this protocol.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Because leukocyte adhesion and transmigration might induce genes in the endothelium either through paracrine cytokine secretion mechanisms or through direct stimulation associated with adhesion, we chose to examine MCP-1 induction in a model using brief, nonlethal ischemia followed by reperfusion that has been well characterized in the past as inducing ROI formation and secretion from myocytes associated with dysfunction but no cell death. 5,[12][13][14] We have also confirmed that there is no significant leukocyte infiltration associated with this protocol.…”
Section: Discussionsupporting
confidence: 68%
“…2,3 Early reperfusion of the ischemic myocardium is a key clinical intervention after myocardial infarction and is attended by a robust inflammatory reaction involving both neutrophils and mononuclear cells. 5,6 It has been shown that late reperfusion, when myocardial salvage is no longer possible, improves myocardial repair and obviates infarct expansion. …”
mentioning
confidence: 99%
“…However, when administered 30 minutes after established coronary microembolization, methylprednisolone no longer prevented leukocyte infiltration, possibly because initial steps of leukocyte activation and leukocyte/endothelium interaction had already occurred. 31,35,36 Glucocorticoids have previously been shown to inhibit the expression of TNF-␣ mRNA in immunologically activated rat peritoneal mast cells, 16 to suppress the production of TNF-␣ in serum and myocardium of lipopolysaccharidestimulated rats, 17 and to abolish the release of TNF-␣ into serum of humans during cardiac surgery. 15 Glucocorticoids also attenuate the infiltration of TNF-␣-producing macrophages/monocytes after coronary microembolization in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings corroborate postmortem histological studies that have demonstrated a time-dependent shift in the location of leukocytes in postischemic myocardium from intravascular (which peaks about 1 hour after reflow) to interstitial (which peaks Ͼ5 hours after reflow). 9,10 Using MCE perfusion imaging with nontargeted microbubbles to assess collateral perfusion within the risk area, we were able to uniquely determine that leukocyte recruitment was attenuated but not completely prevented by collateral flow. These results support previous demonstration of an inverse relation between myocardial blood flow and postischemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These results support previous demonstration of an inverse relation between myocardial blood flow and postischemic inflammation. 10 We anticipated that targeted microbubble imaging in the setting of ischemia/reperfusion would be problematic because microbubble entry into portions of the infarct zone would be prevented by low-or no-reflow. In the first several hours after reflow, however, there is marked heterogeneity of microvascular perfusion within risk area and hyperemia within the infarct region, 11 which should facilitate microbubble entry even within necrotic tissue.…”
Section: Discussionmentioning
confidence: 99%